VD_FINDINFO Jug / 2014 / 216 vom 28. Juli 2014 - VD Tribunal cantonal (2014)
DIVORCE, LIBRE PASSAGEASSURANCES, LOI SUR LE LIBRE PASSAGE, PARTAGESENS GÉNÉRAL, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 30 LPP, 8a al. 1 OLP